PEMANFAATAN DIGITAL MARKETING SEBAGAI MEDIA INFORMASI PEMASARAN ONLINE PRODUK USAHA MIKRO KECIL MENENGAH (UMKM) DI DESA BANGUNJAYA LANGKAPLANCAR - andi kuswandi; Imas Masitoh; Usman Sidiq; Alif Syekhul Munir; Ane Ratna Dewi; Eni Nuraeny; Maulida Hanum (SAHID MENGABDI: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2023)
Doing branding for a company is very important, especially considering the geographical location of Langkaplancar still does not have adequate transportation to move quickly to create marketing traffic plus people's lifestyles that have changed since Covid 19 which implemented PPKM has also changed the way of shopping and searching for imports. only on social media. In addition to the fairly tight competition among MSMEs in the field of presenting the best products, MSMEs are expected to have the ability to promote in the digital world through paid ads so that they can reach consumers with the right targets so that existing products can be offered to the right and targeted consumers. Promotion for a company is a very useful thing to increase consumer awareness of the company being offered, so that it will be widely known and in demand. With the presence of Facebook, Instagram, Shopee, Tokopedia and other applications, many MSMEs have not taken advantage of this media. This is also one of the obstacles for MSMEs to reach a wider range of consumers. Therefore, the implementation of MSME digitization activities is very important, both training and direct practice in advancing MSMEs in Bangunjaya Village. As we all know, Langkaplancar is the most extensive sub-district in Pangandaran district, so it needs promotions that can reach remote areas and comprehensively target consumers in a timely and effective manner.